STRUKTURASI KOMUNIKASI INTERNAL DALAM PRAKTIK MEDIA RELATIONS DI DALAM INDUSTRI MEDIA - Pratama, Brahma Putra (Universitas Negeri Yogyakarta, 2018)
Media relations is one of the practices that can be found in the system of a publicrelations (PR) department. The PR department of a media industry still needs to do thepractice of media relations with other media industry although it has already had its ownchannel to disseminate information. The practice of media relations has aim that theinformation from an organization can be distributed to the public through the channelof the media industry. To achieve the aim, the initial process, such as the interactionand communication in the internal environment of the organization between the PRstaff with the superiors, is required. PR staff and the superiors as the agents use thestructure to act in the process of system production and reproduction. To know howthe process of the system production and reproduction in the interaction of the agentsin the practice of media relations, then analysis using adaptive structuration theorydeveloped by McPhee and Poole is required. This research aims to describe and providean understanding of structuration of internal communication in the practice of mediarelations in the PR department. The method used in this research is a single instrumentalcase study with descriptive qualitative approach. From this study, it is found that in thePR department system, the staff connects to the superiors in the internal environmentin the practice of media relations and the agents use the structure to act and to interactso that the system and practice can take place continuously either as a rountine or as atransformation.Media relations merupakan salah satu praktik yang terdapat dalam sistem departemen public relations (PR). Departemen PR dari suatu industri media ternyata masih perlu melakukan praktik media relations dengan industri media lain meskipun telah memiliki saluran media untuk menyebarkan informasi. Praktik media relations bertujuan supaya informasi dari suatu organisasi dapat disebarluaskan kepada publik melalui saluran suatu industri media. Untuk mencapai tujuan tersebut, diperlukan proses awal berupa interaksi dan komunikasi di lingkungan internal organisasi antara staf PR dengan atasannya. Staf PR dan atasannya sebagai agen menggunakan struktur dalam bertindak dalam proses produksi dan reproduksi sistem. Untuk mengetahui bagaimana proses produksi dan reproduksi sistem tersebut dalam interaksi para agen dalam praktik media relations, maka diperlukan analisis menggunakan teori strukturasi adaptif yang dikembangkan oleh McPhee dan Poole. Penelitian ini bertujuan untuk menggambarkan dan memberikan pemahaman mengenai strukturasi komunikasi internal dalam praktik media relations yang terjadi di dalam departemen PR. Metode yang digunakan dalam penelitian ini adalah studi kasus instrumental tunggal dengan pendekatan kualitatif deskriptif. Dari penelitian ini ditemukan bahwa di dalam sistem departemen PR, staf berhubungan dengan atasannya di lingkungan internalnya dalam melakukan praktik media relations dan para agen menggunakan struktur dalam bertindak dan berinteraksi sehingga sistem dan praktik dapat berlangsung terus-menerus baik sebagai rutinitas maupun sebagai transformasi.Kata kunci: Strukturasi, Komunikasi Internal, Media Relations, Industri Media